Adapting grounded theory to investigate sustainability heritage in informal settlements: Case studies from Islamabad, Pakistan - Shafqat, Ramisa; Marinova, Dora; Khan, Shahed (MDPI AG, 2022)
The paper investigates the sustainability potential of the intangible cultural heritage preserved in informal settlements seen as an extension of rurality in urban settings. It delves into this underexplored dimension of sustainability in the context of the Global South by analysing two informal settlements in Islamabad, Pakistan, namely, France Colony and Mehr Abadi. The grounded theory is adapted by using semistructured interviews during transect walks through the informal settlements followed by a thematic analysis conducted of the experiences, memories, values, religious beliefs, and norms of the dwellers in the two case studies. Four themes are deduced that identify sustainability heritage: (a) values and social practices; (b) communal networks and relationships; (c) built environment and ecology; and (d) remnants of rurality. The study contends that informal settlements are reservoirs of vernacular sustainability elements, and their cultural heritage should be supported instead of imposing planning policies influenced by the North. Culturally specific solutions acceptable to the informal communities are needed to improve the liveability within the city and inform the policy-making process. This requires finding a mechanism for preserving the indigenous regional culture in the informal settlements, their rich heritage, and sustainability-oriented knowledge and practices.